Chromosome‐level genome assembly for the horned‐gall aphid provides insights into interactions between gall‐making insect and its host plant - Hong‐Yuan Wei (Ecology and Evolution, 2022)
Abstract The aphid Schlechtendalia chinensis is an economically important insect that can induce horned galls, which are valuable for the medicinal and chemical industries. Up to now, more than twenty aphid genomes have been reported. Most of the sequenced genomes are derived from free‐living aphids. Here, we generated a high‐quality genome assembly from a galling aphid. The final genome assembly is 271.52 Mb, representing one of the smallest sequenced genomes of aphids. The genome assembly is based on contig and scaffold N50 values of the genome sequence are 3.77 Mb and 20.41 Mb, respectively. Nine‐seven percent of the assembled sequences was anchored onto 13 chromosomes. Based on BUSCO analysis, the assembly involved 96.9% of conserved arthropod and 98.5% of the conserved Hemiptera single‐copy orthologous genes. A total of 14,089 protein‐coding genes were predicted. Phylogenetic analysis revealed that S. chinensis diverged from the common ancestor of Eriosoma lanigerum approximately 57 million years ago (MYA). In addition, 35 genes encoding salivary gland proteins showed differentially when S. chinensis forms a gall, suggesting they have potential roles in gall formation and plant defense suppression. Taken together, this high‐quality S. chinensis genome assembly and annotation provide a solid genetic foundation for future research to reveal the mechanism of gall formation and to explore the interaction between aphids and their host plants.